MENUJU ISLAM MODERNIS: BIM (BARAT-ISLAM_MEDIA) SEBAGAI JAWABAN DI TENGAH KRISIS MANUSIA MODERN - Dwi Sri Handayani (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2021)
Modernization or modern civilization is a condition where there is an increase or development in various aspects of society. But despite these developments many negative values arise from modernization. Modernization should not only bring world conditions that are increasingly sophisticated from the perspective of the means and facilities of life, but also offer new values that are modern and progressive. Values that can shape modern humans in order to answer the challenges of the times. Seeing modern civilization today which is increasingly leaning towards negative both in terms of thought, behavior, and the nature of the question is how Islam exists as a solution amid modernization of the many problems that arise. Then the authors offer the concept of BIM as a solution amid the crisis of modern humans from modernization. By using a normative approach, as well as studying the library (library research) as a type of research. The author tries to combine the concepts of the West, Islam, and Applied using media intermediaries toshape modern humans as a step towards Modernist Islam. The result of this research is the suitability of using the BIM concept as an alternative solution for modern humans to face global modernity in order to move towards modernist Islam.